Increased frequency of restless legs syndrome in atopic dermatitis - Cicek, D.; Halisdemir, N.; Dertioglu, S. B.; Berilgen, M. S.; Ozel, S.; Colak, C. (Wiley, 2012)
Background. Restless legs syndrome (RLS) is characterized by an unpleasant sensation in the legs, which is difficult to describe, but produces an urge to move the legs frequently. Aim. To assess the prevalence and severity of RLS in patients with atopic dermatitis (AD) and patients with psoriasis, and to investigate the factors potentially associated with RLS. Methods. In total, 253 people were enrolled (120 with AD, 50 with psoriasis and 83 healthy controls). A diagnosis of RLS was made according to the criteria of the International RLS Study Group (IRLSSG), and severity was assessed using the IRLSSG severity scale. Results. RLS was significantly more common in patients with AD (40.8%) than in patients with psoriasis (18.0%) or in controls (10.8%) (P < 0.01 and P < 0.001, respectively). Prevalence of RLS was higher in patients with active AD than in those with inactive AD (55.3% vs. 23.6%) or controls. There was a significant difference in RLS prevalence between patients with active and those with iactive AD, between patients with active AD and healthy controls, between patients with active AD and patients with psoriasis, and between patients with inactive AD and healthy controls (P < 0.001, P < 0.001, P < 0.001, P = 0.04, respectively). There was no significant difference in RLS prevalence between patients with active AD and patients with psoriasis, or between patients with psoriasis and healthy controls (P > 0.05). Of patients who were positive for RLS, 56.9% had a family history of atopy and 40.3% had a family history of RLS, and there was a significant relationship between the presence of RLS and family history of atopy or RLS (P < 0.001 for both). Conclusions. RLS is common in patients with AD, particularly in those with active disease.
Keywords: Clinical Characteristics; Prevalence; Epidemiology; Bupropion; Psoriasis; Validation; Pregnancy; Symptoms; Quality; Disease